2010
DOI: 10.5194/adgeo-25-85-2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationships of heavy rains in the Czech Republic

Abstract: Abstract. Study of heavy rain events and their spatial distribution are of great importance. Such events cause local flooding, accelerate soil erosion and cause damage on property. Data for this study were derived by Sokol and Bližňák (2009) from radar reflectivity and daily rain gauge measurements for the period of 2002–2008. We selected heavy rain events using spatial and intensity constrains. We studied relationships between heavy rains, altitude and terrain roughness. Heavy rain totals correlate with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Although the best formulas for event depth and number of events reported in Table III include total rainfall depth, the regressions considering altitude as an explanatory variable are also significant (with coefficients of determination of 0.52 and 0.2 for the relationship between event depth and number of events to altitude, respectively). Sokol and Bli z nák (2009) and Bek et al (2010) also mentioned only a weak and insignificant relationship of rain rate to altitude, which is in agreement with our results.…”
Section: Rain Event Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…Although the best formulas for event depth and number of events reported in Table III include total rainfall depth, the regressions considering altitude as an explanatory variable are also significant (with coefficients of determination of 0.52 and 0.2 for the relationship between event depth and number of events to altitude, respectively). Sokol and Bli z nák (2009) and Bek et al (2010) also mentioned only a weak and insignificant relationship of rain rate to altitude, which is in agreement with our results.…”
Section: Rain Event Characteristicssupporting
confidence: 92%
“…Sokol and Bližňák () and Bek et al . () also mentioned only a weak and insignificant relationship of rain rate to altitude, which is in agreement with our results.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…() processed rain gauge data obtained from 1961 to 2000 and mainly focused on long‐term precipitation means, because sub‐daily station data were scarce at that time. Subsequent studies (Sokol and Bližňák, ; Bek et al ., ) have confirmed that radar‐derived precipitation estimates can be successfully employed to better understand the relationships between altitude and precipitation intensities.…”
Section: Introductionmentioning
confidence: 54%